A Conversation : .., A Contact - Mwanaka, Tendai R. (Book collections on Project MUSE., 2018)
A Conversation..., A Contact has 22 fiction pieces around themes to do with political struggle, love relationships, heartbreaks and the resulting breakdowns, dreams, folklores, life, spirituality, anger, hate, grief, and all sorts of other human breaths.